The Relationship between School Social Environment and Mental Health of Adolescents - Cahyadi, Anggih Tri; Sulistyaningtyas, Nunik; Hairunis, Mirham Nurul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The mental health of school children is gaining increasing attention, particularly concerning the social environment at school. This social environment encompasses various aspects such as peer interactions, relationships with teachers, and the overall school climate. These factors have a significant impact on children's mental health, including their emotional, psychological, and social well-being. Peer interaction is a key component of the school’s social environment. Positive relationships with peers can provide emotional support, boost self-confidence, and help children develop important social skills. Conversely, negative experiences such as bullying or social isolation can lead to stress, anxiety, and depression. The purpose of this study is to examine the relationship between the school social environment and the mental health of adolescents. This study uses a quantitative research approach with a cross-sectional design. The respondents of this study were 33 samples. The results of the statistical test showed that there is a significant relationship between the school social environment and students' mental health, with a p-value of 0.01, which is less than the significance threshold of 0.05. It can be concluded that the school social environment has a significant impact on students' mental health.